2015
DOI: 10.3390/en8021025
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Distribution of Solar Radiation on a Two-Axis Tracking Plane for Photovoltaic Conversion

Abstract: Abstract:The paper presents selected isotropic and anisotropic mathematical models to calculate the distribution of solar radiation on the photovoltaic module plane with any spatial orientation. A comparison of solar radiation models for Poland is based on measured data and received from the Institute of Meteorology and Water Management. Power density of solar radiation for different angular positions, especially for representative days of each month, was calculated. Based on the statistical analysis of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The method of determination of the recommended days of the year with their calculation for the typical meteorological year of Poznan was presented in [38]. 18.01.2015) with strongly random distribution of the surface density of the solar power radiation.…”
Section: Results Of Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The method of determination of the recommended days of the year with their calculation for the typical meteorological year of Poznan was presented in [38]. 18.01.2015) with strongly random distribution of the surface density of the solar power radiation.…”
Section: Results Of Statistical Analysismentioning
confidence: 99%
“…Due to strongly stochastic character of obtaining energy (sunlight depending on seasons of the year, weather conditions, etc. ), the results of the conducted tests were subject to statistical processing, which constitutes the main part of this article [4,5,[37][38][39][40][41][42][43]]. …”
Section: Introductionmentioning
confidence: 99%
“…Isotropic models (Liu-Jordan, Badescu, Koronakis, Tian) and anisotropic models (Hay, Steven and Unsworth) were used to estimate the distribution of radiation power on photovoltaic planes slanted at 30 • , 45 • , and 60 • facing south. The outcomes demonstrated that the anisotropic models facilitated obtaining higher radiation throughout the year in comparison to isotropic models for the Polish latitude [65].…”
Section: Recognizing Accurate Models For Estimation Of Diffuse Radiatmentioning
confidence: 89%
“…The two models differ by the way they determine the diffuse component of the radiation incident on a tilted plane. In the Hay model, the diffuse irradiance is divided into an isotropic contribution, and a "circumsolar" part, which is proportional to the beam component [21][22][23][24][25]. On the other hand, Perez-Ineichen model introduces the "horizon band" as a third diffuse component [19,26].…”
Section: Introductionmentioning
confidence: 99%